PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS MACROMEDIA FLASH MENGGUNAKAN PENDEKATAN OPEN ENDED PROBLEM PADA MATERI BANGUN RUANG - Zamzam, Kenys Fadhilah (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
This research aim to see the development of interactive multimedia based on macromedia flash using an open-ended problem approach in the material of building space with. The research method used was research and development methods using 4D models. The results of the assessment from material experts include: aspects on the quality of content obtained an average result of 80 where the criteria are good, the design of the developed interactive multimedia obtained an average of 85.67 in the very good category, aspects of open ended problems obtained average results The average shows 84.25 which is in the very good category, as well as the language aspect and interactive multimedia display developed an average of 81.77 where the categories obtained are very good. The results of media experts show an average interactive multimedia design of 86 which is in the very good category, multimedia content is on average 82.36 with very good criteria, the display shows 88.56 where the criteria are very attractive, and the average convenience operation is 87 showing very interesting criteria. Therefore, interactive multimedia that has been developed is feasible and ready to be tested. After being tested on 10 students, it was obtained data that the average student was in the very good category or said to have completed learning. Broadly speaking, interactive multimedia, which is based on macromedia flash, uses an open-ended problem approach to the effective spatial structure used in the learning process as a medium.